2021
DOI: 10.1111/papr.13055
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic axial back pain with 60‐day percutaneous medial branch PNS: Primary end point results from a prospective, multicenter study

Abstract: Background:The objective of this prospective, multicenter study is to characterize responses to percutaneous medial branch peripheral nerve stimulation (PNS) to determine if results from earlier, smaller single-center studies and reports were generalizable when performed at a larger number and wider variety of centers in patients recalcitrant to nonsurgical treatments. Materials & Methods:Participants with chronic axial low back pain (LBP) were implanted with percutaneous PNS leads targeting the lumbar medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 64 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…19 Moreover, recent studies have demonstrated the role of PNS in peripheral and central analgesic mechanisms by modulating the inflammatory pathways, autonomic nervous system, endogenous pain inhibition pathways, and cortical and subcortical areas. 20,21 The ASPN society formed an international multidisciplinary panel consisting of anesthesiologists, neurosurgeons, and pain medicine physicians who are experts in the field of PNS neuromodulation to create these consensus practice guidelines. To qualify for inclusion on the expert panel, each author was required to have experience with performing PNS trials and lead implantation, publications and ongoing research pertaining to PNS neuromodulation, and impact on the field of neuromodulation.…”
Section: Indicationsmentioning
confidence: 99%
“…19 Moreover, recent studies have demonstrated the role of PNS in peripheral and central analgesic mechanisms by modulating the inflammatory pathways, autonomic nervous system, endogenous pain inhibition pathways, and cortical and subcortical areas. 20,21 The ASPN society formed an international multidisciplinary panel consisting of anesthesiologists, neurosurgeons, and pain medicine physicians who are experts in the field of PNS neuromodulation to create these consensus practice guidelines. To qualify for inclusion on the expert panel, each author was required to have experience with performing PNS trials and lead implantation, publications and ongoing research pertaining to PNS neuromodulation, and impact on the field of neuromodulation.…”
Section: Indicationsmentioning
confidence: 99%
“…Percutaneous PNS of the LMBN is a relatively new modality, and to date, there are 10 human, clinical studies focusing on nonspinal neuromodulation for chronic axial LBP (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Kapural et al (25) was the first to publish clinical data using the SPRINT device.…”
Section: Discussionmentioning
confidence: 99%
“…Low-frequency pulse train stimulation of the LMBN terminal branches activates both sensory afferents and muscle efferent fibers, producing proprioceptive signals in large diameter fibers that convergently directly activate sensory afferents engaging in the spinal cord gating mechanism. Data are limited but have demonstrated sustained results, even after cessation of 60-day temporary stimulation for patients with multifactorial chronic axial low back pain, including degenerative disc disease, lumbar spondylosis, lumbar facet arthropathy, discogneic pain, etc (17,(20)(21)(22)(23)25). The permanently implanted restorative LMBN PNS system, on the other hand, has a more regimented minimally invasive technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17-20 Additionally, there is some growing evidence to support the use of PNS as a non-opioid therapy to assist in the treatment of chronic axial back pain as well as other neuropathic pain conditions. [20][21][22] Studies on the use of PNS for chronic pain conditions continue to demonstrate that peripheral nerve stimulation can lead to significant improvement in pain and…”
Section: Discussionmentioning
confidence: 99%